Carbonate-rich dendrolitic cones: insights into a modern analog for incipient microbialite formation, Little Hot Creek, Long Valley Caldera, California. (December 2017) - Bradley, James; Daille, Leslie; Trivedi, Christopher; Bojanowski, Caitlin; Stamps, Blake; Stevenson, Bradley; Nunn, Heather; Johnson, Hope; Loyd, Sean; Berelson, William; Corsetti, Frank; Spear, John
Abstract Ancient putative microbial structures that appear in the rock record commonly serve as evidence of early life on Earth, but the details of their formation remain unclear. The study of modern microbial mat structures can help inform the properties of their ancient counterparts, but modern mineralizing mat systems with morphological similarity to ancient structures are rare. Here, we characterize partially lithified microbial mats containing cm-scale dendrolitic coniform structures from a geothermal pool ("Cone Pool") at Little Hot Creek, California, that if fully lithified, would resemble ancient dendrolitic structures known from the rock record. Light and electron microscopy revealed that the cm-scale 'dendrolitic cones' were comprised of intertwined microbial filaments and grains of calcium carbonate. The degree of mineralization (carbonate content) increased with depth in the dendrolitic cones. Sequencing of 16S rRNA gene libraries revealed that the dendrolitic cone tips were enriched in OTUs most closely related to the generaPhormidium, Leptolyngbya, andLeptospira, whereas mats at the base and adjacent to the dendrolitic cones were enriched inSynechococcus . We hypothesize that the consumption of nutrients during autotrophic and heterotrophic growth may promote movement of microbes along diffusive nutrient gradients, and thus microbialite growth. Hour-glass shaped filamentous structures present in the dendrolitic cones may have formed around photosynthetically-produced oxygen bubbles—suggesting that mineralization occurs rapidly and on timescales of the lifetime of a bubble. The dendrolitic-conical structures in Cone Pool constitute a modern analog of incipient microbialite formation by filamentous microbiota that are morphologically distinct from any structure described previously. Thus, we provide a new model system to address how microbial mats may be preserved over geological timescales. Paleobiology: modern microbes may tell an ancient tale Microbial mats currently thriving in a hot pool in California may help explain the origin of fossilized evidence of early life on Earth. Modern microbial mats that are structurally similar to microbial fossil mats are rare. John Spear at the Colorado School of Mines, with co-workers from elsewhere in the USA and in Chile, examined the microbial mats growing in a geothermal pool at Little Hot Creek in California. Light microscopy and electron microscopy identified crucial fine structure similarities with branching mat structures in the fossil record. The researchers developed hypotheses to explain the influence of nutrient flow on the growth and movement of the microbes in the mats. These living mats are a useful model system to help researchers understand how ancient microbial mats formed and were preserved over geological timescales.